PENGARUH SP-36 DAN ASAM HUMAT TERHADAP PERTUMBUHAN DAN PRODUKSI TANAMAN KEDELAI ( Glycine max L) - Fajar Setyawan; Feri Setyawan (BUANA SAINS, 2019)
Soybean is a food crop commodity that is needed by the Indonesian population because it is a source of vegetable protein, fat, vitamins, and minerals. To increase soybean production one of the things that needs to be done is the addition of phosphorus to increase the density of soybean seeds. The purpose of this study was to determine the effect of interactions between the administration of SP36 fertilizer doses and humic acid doses on the growth and production of soybean (Glycine max L) Dega 1 variety. Plosoklaten, Kediri Regency, with a height of 105 meters above sea level, with sandy loam soil type with soil pH 5. The study used factorial randomized block design (RBD) consisting of two factors, repeated 3 times. Parameters observed were Plant dried weight, plant growth rate, number of pods/plants, the weight of Seeds per plot, yield, observation data were analyzed using analysis of variance (F test). The results of the analysis of the real variance were continued with the Significant Difference test at a 5% significance level to find out the difference between treatments. The first factor is SP36 fertilizer and the second factor is humic acid. Based on the results of research that has been done, there was an interaction between the administration of SP36 fertilizer and humic acid in the parameters of plant dry weight at the age of 14 and 21, number of pods, seed weight per plot and yield., Giving fertilizer SP36 200 kg /ha with humic acid 50kg / ha can increase crop production by 43% compared to without SP36 and without humic acid.